2006
DOI: 10.1002/cncr.22204
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acute myelogenous leukemia with outpatient azacitidine

Abstract: BACKGROUNDPatients older than 55 years of age with acute myelogenous leukemia (AML) are less likely to achieve complete remission and more likely to experience toxicity with conventional induction chemotherapy than younger patients. Azacitidine administered in the outpatient setting is well tolerated and can induce complete hematological remission in patients with myelodysplastic syndromes (MDS). At higher doses, azacitidine has activity in AML.METHODSTwenty patients were retrospectively identified who had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 19 publications
4
44
1
2
Order By: Relevance
“…34 However, the CR/CRi rate in evaluable patients of 44% in this study (39% for total patients) exceeds the reported CR rate for azacitidine alone (20%), 12 and the CR/CRi rate for lenalidomide alone (30%). 18 Results from the phase-2 portion of this study will more accurately determine the response rate associated with the sequential combination of azacitidine and lenalidomide, allowing a more direct comparison.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…34 However, the CR/CRi rate in evaluable patients of 44% in this study (39% for total patients) exceeds the reported CR rate for azacitidine alone (20%), 12 and the CR/CRi rate for lenalidomide alone (30%). 18 Results from the phase-2 portion of this study will more accurately determine the response rate associated with the sequential combination of azacitidine and lenalidomide, allowing a more direct comparison.…”
Section: Discussioncontrasting
confidence: 61%
“…Azacitidine, an azanucleoside DNA methyltransferase inhibitor that is approved by the US Food and Drug Administration in the related myeloid malignancy myelodysplastic syndrome (MDS), 11 is associated with a low response rate (B20%) in elderly AML patients. 12 Lenalidomide is an immunomodulatory agent, Food and Drug Administration approved for use in MDS with del(5q) and in multiple myeloma. 13 In various diseases it regulates immune responses, gene expression, phosphatase activity, angiogenesis and cytokines, 13 --16 and has demonstrated single-agent activity when used as primary and salvage therapy in AML.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted on 149 AML patients having a poor cytogenetic structure, WBC [ 15 000/ll, the ECOG performance score C2, and the response to therapy were determined to be the factors influencing overall survival [13]. When the side effects were analyzed in both treatment groups, a statistically significant difference was not detected between treatment-related neutropenia, thrombocytopenia, anemia, the amount of blood transfusion, grade of infection, diarrhea, skin reaction, hospitalizationrequiring infection, and duration of hospital stay, and this is consistent with the literature [11,21,22].…”
Section: Discussionsupporting
confidence: 78%
“…Parenteral azacitidine has been extensively evaluated in patients with MDS, chronic myelomonocytic leukemia (CMML), and AML in large randomized clinical trials,5, 6, 7 in regional registry studies,8, 9, 10, 11, 12, 13 and in numerous smaller retrospective analyses of patients treated in community practice 14, 15. These studies show azacitidine reduces cytopenias in select lower‐risk MDS and prolongs overall survival (OS) in higher‐risk MDS and AML,5, 6, 7, 16 may be effective maintenance therapy after induction chemotherapy (IC) or allogeneic hematopoietic stem cell transplant (alloHSCT),17, 18, 19, 20 and can induce responses in patients with relapsed/refractory disease 12, 21.…”
Section: Introductionmentioning
confidence: 99%